(untitled) (Journal of Engineering, 2021)
Sewage water is a mixture of water and solids added to water for various uses, so it needs to be treated to meet local or global standards for environmentally friendly waste production. The present study aimed to analyze the new Maaymyrh sewage treatment plant’s quality parameters statistically at Hilla city. The plant is designed to serve 500,000 populations, and it is operating on a biological treatment method (Activated Sludge Process) with an average wastewater inflow of 107,000m3/day. Wastewater data were collected daily by the Mayoralty of Hilla from November 2019 to June 2020 from the influent and effluent in the (STP) new in Maaymyrh for five water quality standards, such as (BOD5), (COD), (TSS), (TP) and (TN). The results showed that the removal efficiency was 88%, 75%, 94%, 57%, and 77%, respectively. The results of the cluster analysis (CA) showed the formation of clusters in four stages and then gave the final shape consisting of two groups. At the same time, two influencing factors were extracted in the principal component analysis (PCA). The effluent’s final quality (an average of eight consecutive months) complies with the stringent regulations proposed in the Iraqi Quality Requirements.